Strong Crystallographic Influence on Spin Hall Mechanism in PLD-Grown IrO2 Thin Films - Pilar Jiménez-Cavero; Irene Lucas; Jorge Ara-Arteaga; M. Ricardo Ibarra; Pedro A. Algarabel; Luis Morellón (Nanomaterials, 2021)
Spin-to-charge conversion is a central process in the emerging field of spintronics. One of its main applications is the electrical detection of spin currents, and for this, the inverse spin Hall effect (ISHE) has become one of the preferred methods. We studied the thickness dependence of the ISHE in iridium oxide (IrO<semantics>2</semantics>) thin films, producing spin currents by means of the spin Seebeck effect in <semantics>γ−</semantics>Fe<semantics>2</semantics>O<semantics>3</semantics>/IrO<semantics>2</semantics> bilayers prepared by pulsed laser deposition (PLD). The observed ISHE charge current density, which features a maximum as a consequence of the spin diffusion length scale, follows the typical behaviour of spin-Hall-related phenomena. By fitting to the theory developed by Castel et al., we find that the spin Hall angle <semantics>θSH</semantics> scales proportionally to the thin film resistivity, <semantics>θSH∝ρc</semantics>, and obtains a value for the spin diffusion length <semantics>λIrO2</semantics> of <semantics>λIrO2=3.3(7)</semantics> nm. In addition, we observe a negative <semantics>θSH</semantics> for every studied thickness and temperature, unlike previously reported works, which brings the possibility of tuning the desired functionality of high-resistance spin-Hall-based devices. We attribute this behaviour to the textured growth of the sample in the context of a highly anisotropic value of the spin Hall conductivity in this material.